Effect of democracy on health: ecological study (2004)
ABSTRACT: Although the influence of democracy in preventing famines has been reported, there have been no empirical studies on the relation between the extent of freedom allowed by political regimes and the effect on a nation’s health. We explored the effect of democracy on life expectancy and maternal and infant mortality in most countries, taking into account a country’s wealth, its level of inequality, and the size of its public sector.